FUZZY CALCULUS: A COMPREHENSIVE LITERATURE REVIEW - Efendi; Admi Nazra; Mahdhivan Syafwan; Haripamyu (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
This report presents a literature review on Fuzzy Calculus, a field that emerged from the integration of classical calculus with fuzzy set theory. Classical calculus, although fundamental for modeling precise systems, has limitations in dealing with the uncertainty and ambiguity inherent in real-world phenomena. Fuzzy calculus extends the concepts of derivative and integral to the fuzzy domain, enabling modeling of dynamic systems involving uncertain variables. This report outlines the basic concepts, methodologies of fuzzy differentiation and integration, and highlights significant opportunities in dynamic systems modeling, optimization, control systems, artificial intelligence, and various cross-disciplinary case studies. In addition, theoretical and practical challenges including unique operation definitions, lack of standardization, result interpretation issues, and computational complexity are discussed. Finally, it presents future research directions of Fuzzy Calculus in the face of complexity and uncertainty in the modern world.